THE EFFECT OF INTELLECTUAL INTELLIGENCE (IQ), SPIRITUAL INTELLIGENCE (SQ), EMOTIONAL INTELLIGENCE (EQ) ON THE LEVEL OF UNDERSTANDING ACCOUNTING STUDENT TAXPAYER UNISMUH MAKASSAR - Riski Wulandari; Masrullah, Masrullah; Khadijah Darwin (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine how Intellectual Intelligence (IQ), Spiritual Intelligence (SQ) and Emotional Intelligence (SQ) affect the Level of Understanding of Unismuh Makassar Accounting Students regarding Taxpayers. The type of data used in this study was quantitative data obtained from questionnaires distributed. The population and sample in this study are accounting students of the class of 2020 and 2021. This sampling technique uses purposive sampling. In this study, the data sources used include primary data. The research instrument used in this study used the Likert scale method. Based on the results of research using statistical calculations through the Statisticall Package for the Social Science (SPSS) version 22 application that the probability for intellectual intelligence variables is 0.021, which is smaller than 0.05. With a tcount of 2.352 greater than ttable 1.66123.. The probability for an intellectual intelligence variable is 0.000, which is smaller than 0.05. With a tcount of 12.420 greater than ttable 1.66123. The probability for an emotional intelligence variable is 0.000, which is smaller than 0.05. With a tcount of 64.439greater than ttable 1.66123. Intellectual Intelligence (IQ), Spiritual Intelligence (SQ), and Emotional Intelligence (EQ) have a significant positive effect on the understanding of accounting student taxpayers of Unismuh Makassar.